2010
DOI: 10.1111/j.1747-0803.2009.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Adults with Down Syndrome: Safety and Long-term Outcome of Cardiac Operation

Abstract: Objective. As limited data exist, we sought to review the safety and outcome of cardiac surgery in the adult Down syndrome population. Design. We reviewed the data of all patients Ն18 years old with Down syndrome who underwent cardiac surgery at our hospital. Results. Fifty patients underwent 57 surgeries (mean age 33 years). Fifteen patients had prior cardiac operations in childhood: 7 complete and 1 partial atrioventricular canal, 2 secundum atrial septal defect, 2 Tetralogy of Fallot, 1 patent ductus arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
0
21
0
5
Order By: Relevance
“…[2,3] Previously, Nisli et al, [3] evaluated the incidence and types of coronary heart disease patterns in the Turkish children with Down syndrome. The authors reported that, in 421 patients with Down syndrome, 77.6% had a single cardiac lesion, while the remaining 22.4% had multiple defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2,3] Previously, Nisli et al, [3] evaluated the incidence and types of coronary heart disease patterns in the Turkish children with Down syndrome. The authors reported that, in 421 patients with Down syndrome, 77.6% had a single cardiac lesion, while the remaining 22.4% had multiple defects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Several studies have shown that the probability of concomitant emergence of congenital disorders with Down syndrome as high as 44%. [1] Although complex forms of cardiovascular anomalies, such as atrioventricular canal defects and ventricular septal defects (VSDs) are diagnosed in the early postnatal period, atrial septal defects (ASDs) may present with an incidence of about 16.7% in adulthood.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Jelentősen meghosszabbodott az élet-koruk; például az Amerikai Egyesült Államokban 1983-tól 1997-ig átlagéletkoruk 25 évről 49 évre emelkedett [8], míg Európában Bittles és mtsai [9] szerint 40 év alatt 12 évről 60 évre. Majdalany és mtsai [10] szerint a betegek 14%-a már megéri a 70 éves életkort.…”
Section: Megbeszélésunclassified